Dietary partitioning in sympatric Paradoxurinae civets in Borneo suggested by compound-specifc nitrogen isotope analysis of amino acids - Miyabi Nakabayashi; Takumi Tsutaya; Abdul Hamid Ahmad; Yoko Sasaki; Nanako O. Ogawa; Naoto F. Ishikawa; Naohiko Ohkouchi (BioMed Central Ltd, 2024)
We applied stable carbon and nitrogen isotopic analyses to understand the faunivory of the four sympatric wild Paradoxurinae civet species in Borneo, which share similar ecological characteristics. We also employed compoundspecifc nitrogen isotope analysis of amino acids to estimate these species’ trophic positions (TPs). The bulk stable isotope analysis revealed distinctly lower nitrogen isotope ratios in binturongs than in the other three species. This suggests that binturongs exhibit the lowest degree of faunivory among the four species. Binturongs had the lowest TP estimated from the nitrogen isotope ratios of amino acids (2.0–2.1), followed by small-toothed palm civets (2.4–2.5), masked palm civets (2.7), and common palm civets (2.9). These results suggest that there is little faunivory in binturong and variations in faunivory in the other species. Although the number of samples measured for the nitrogen isotope ratios of amino acids is small (n=2 for each species), our results suggest that the varying degree of consumption of animal food sources, such as insects, is the key mechanism of niche partitioning in these four Paradoxurinae civet species in Borneo. Such subtle but essential diferences in closely related sympatric species would maintain high biodiversity in tropical regions